Storytelling Methods and Learning Styles on Early Childhood Speaking Skills - Satriani; Herlina; Herman; Wahira; Surya (Indonesian Journal Publisher, 2026)
This study aims to analyze the influence of storytelling methods on early childhood speaking ability in several early childhood schools, to analyze the influence of learning style on early childhood speaking ability, and to analyze the influence of storytelling methods and learning styles on early childhood speaking ability. The method in this study uses This type of research uses a quantitative research approach. The design in this study uses a case study design which is a method to collect and analyze data related to a case. The techniques used in data collection include, observation, documentation, questionnaires. The data analysis used was in the form of descriptive analysis, validity and reliability test, classical assumption test, and multiple linear regression analysis. The results of the study show that there is a positive and significant influence between storytelling methods on children's learning abilities, there is a positive and significant influence between learning styles on children's learning abilities. Based on the results of the study using the F test, it shows that the storytelling method and learning style simultaneously have a significant influence on the ability of early childhood learning in early childhood schools. As a suggestion for teachers to pay attention to the emotional involvement and active involvement of students, so that the storytelling method applied can encourage students to feel and express their feelings and provide opportunities for students to retell the content of the story in the words of the students.